2016
DOI: 10.1111/cdev.12617
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Interpersonal Stress: Normative Changes Across Childhood and the Impact of Peer Victimization

Abstract: This research examined the development of stress responses across 2nd to 6th grades and whether exposure to peer victimization alters stress response trajectories. Youth (338 girls; 298 boys; M age = 7.97 years, SD = .37) reported on stress responses; teachers and youth reported on peer victimization. Latent growth curve modeling revealed an increase in effortful engagement responses and a decrease in disengagement and involuntary engagement responses during this period. Peer victimization disrupted these norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 71 publications
(89 reference statements)
1
15
0
Order By: Relevance
“…Another study, for example, found in a meta-analysis of longitudinal scholarships substantial relationships between peer victimization and succeeding variations in internalizing problems [2], while other researchers found that peer victimization is connected to adjustment difficulties in youth, including violent behavior [1]. Likewise, other scholars in their research found that peer victimization facilitates stress in youth by intruding on the development of effective managing while fostering maladaptive strain responses [3]. Similar to the findings of the current research study, others found differences in approach and avoidant responses with regard to peer victimization [6], while additional researchers [5] identified two-way connections between peer harassment and boys’ self-blame and girls’ wishful thinking with regard to the willingness to intervene in violent events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study, for example, found in a meta-analysis of longitudinal scholarships substantial relationships between peer victimization and succeeding variations in internalizing problems [2], while other researchers found that peer victimization is connected to adjustment difficulties in youth, including violent behavior [1]. Likewise, other scholars in their research found that peer victimization facilitates stress in youth by intruding on the development of effective managing while fostering maladaptive strain responses [3]. Similar to the findings of the current research study, others found differences in approach and avoidant responses with regard to peer victimization [6], while additional researchers [5] identified two-way connections between peer harassment and boys’ self-blame and girls’ wishful thinking with regard to the willingness to intervene in violent events.…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies have explored the relationship between victimization, including peer violence, and both behavioral consequences and emotional adjustment. Results have suggested that many youths will exhibit subsequent internalizing symptoms and disruptive behavior in response to patterns of violent events [1,2,3]. With regard to exposure to violence, many youths are the primary witnesses to criminal activity in disadvantaged settings, while peer violence and other forms of direct victimization remain prevalent primarily among those between the ages of 12–18 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, vulnerability to depressive symptoms, as well as differences in depression between youth of depressed and nondepressed mothers, may depend on age. In addition, adolescence is a time when youth become increasingly focused on peer relationships (Hergovich, Sirsch, & Felinger, 2002; Steinberg & Silverberg, 1986) and develop greater coping and emotion regulation capabilities (Troop-Gordon, Sugimura, & Rudolph, in press; for reviews, see Compas et al, 2001; Zeman, Cassano, Perry-Parrish, & Stegall, 2006). Consequently, youth responses to peer stress may have more important implications for depression among older than younger adolescents.…”
Section: Alternative Moderating and Explanatory Variablesmentioning
confidence: 99%
“…Early adolescence and the transition to middle school are crucial to investigate due to developmental changes in coping capacities and peer experiences. For example, compared to younger children, early adolescents are capable of more flexible and sophisticated cognitive strategies, such as planful problem‐solving (Troop‐Gordon, Sugimura, & Rudolph, ) and cognitive distraction in addition to behavioral distraction (Skinner & Zimmer‐Gembeck, ; Zimmer‐Gembeck & Skinner, ). Early adolescents also increasingly seek social support from peers (Skinner & Zimmer‐Gembeck, ; Zimmer‐Gembeck & Skinner, ).…”
Section: Introductionmentioning
confidence: 99%